Análise da atuação dos diretores de escola na perspectiva do patrimonialismo - Peres, Ana Paula Franzini (2009)
The present project has for objective to understand the politics dimension of the function/post of the principal (headteacher), as well as its joint with the City department of Education and the pertaining to school community. For such, we made study of the patrimonialism as Portuguese inheritance; of a present patrimonialism system in Brazil since the settling. We analyze the way to enter of the position/job in special in Araraquara/SP s city, where we concentrate the research, noticing the clientelism and patrimonialism internally in the educational units through the figure of the principal (headteacher). We concentrate in the process of construction of the principal s patrimonialist character, with intention to contribute to delineated a direction for a really democratic management in the schools. In this context, we look for to understand our patrimonialist inheritance Portuguese existing until today in the school. We conclude that the headteacher is inserted in a culture that loads pieces of patrimonialism and clientelism, of a centralizer power culture, and all the responsibilities of college are of him. The administrative structure to school put the principal on top of the hierarchy, contributing that the structures of power remain in the same way.